Fabrication and feasibility study of an absorbable diacetyl chitin surgical suture for wound healing. Issue 1 (10th February 2015) - Shao, Kai; Han, Baoqin; Gao, Jinning; Jiang, Zhiwen; Liu, Weizhi; Liu, Wanshun; Liang, Ye
Abstract: Diacetyl chitin (DAC) is an acidylated chitin obtained using acetic anhydride mixed perchloric acid system. By wet spinning and weaving technique, DAC has been successfully developed into a novel absorbable surgical suture. Thanks to the unique properties of chitins, the potential application of this novel monocomponent multifilament DAC suture may break the monopoly of synthetic polymer sutures in wound closure area. In this study, DAC was synthesized and characterized by multiple approaches including elemental analysis, Fourier transform infrared spectrometry (FTIR), and X‐ray diffraction (XRD). In addition, we performed the feasibility assessment of DAC suture (USP 2‐0) as absorbable suture for wound healing. Several lines of evidences suggested that DAC suture had comparable mechanical properties as synthetic polymer sutures. Moreover, DAC suture retained approximately 63% of the original strength at 14 days and completely absorbed in 42 days with no remarkable tissue reaction in vivo . Most important of all, DAC suture significantly promoted skin regeneration with faster tissue reconstruction and higher wound breaking strength on a linear incisional wound model. All these results demonstrated the potential use of DAC suture in short‐ or middle‐term wound healing, such as epithelial and connective tissue. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 2016:104B:116–125.